The state of radicalization, extremism, and violent extremism in Malaysia, 2021-2022 - El-Muhammady, Ahmad (2022)
The presentation discusses on the current updates on the radicalization, extremism and violent extremism cases in Malaysian from 2021 until 2022 (February).